The Effect Knowledge Management and Entrepreneurship Orientation on Organizational Performance Through Innovation - Wati, Hernum Daya; Rofiaty, Rofiaty; Moko, Wahdiyat (Interdisciplinary Social Studies, 2022)
ackground: Village-Owned Enterprises (BUMDes) are believed to have many benefits for rural communities. Village economic development has become a major concern for the government, especially in developing countries, including Indonesia. Aim: This research discusses Knowledge Management, Entrepreneurial Orientation, and Innovation on the Performance of Village-Owned Enterprises. Method: A sample of 42 Village-Owned Enterprises (BUMDes) in Bojonegoro Regency, including the Chairman, Secretary, and Treasurer who are directly involved in strategic decision making in the organization. Based on these data, SmartPLS 4.0 Software processes structural parameter estimates according to the relationship model as described in the conceptual framework of the study. Findings: The results showed that Entrepreneurship and Innovation Orientation has a positive and significant effect on Organizational Performance, but Knowledge Management does not have a positive and significant effect on Organizational Performance. Meanwhile, Innovation becomes the Full Mediation of Knowledge Management to Organizational Performance. Then Innovation becomes a Partial Mediation of Entrepreneurial Orientation towards Organizational Performance.